Human development in South Africa: De La Rey, C, Duncan, N, Shefer, T, van Niekerk, A (eds) (1997) Contemporary issues in human development: A South African focus. Johannesburg: International Thomson Publishing. - Bhana, Arvin (PINS-Psychology in Society, 2026)
Attempts by South African scholars to write for local contexts is an emerging trend that needs greater encouragement. This book is a good example of the scholarship that lies largely untapped within South African academia. For many South African writers, not only must they overcome a complex of "international is better" syndrome, but also have to deal with all the prejudices inherent to South African academia. This book succeeds excellently in holding a model of "best practice" that enables "marginalised" academics to write on topics taking account of South African realities.